Factors affecting project governance in ethical decision making for public sector project procurement : a delphi study / Aliza Abu Hassim, Stephen Kajewski and Bambang Trigunarsyah - Abu Hassim, Aliza; Kajewski, Stephen; Trigunarsyah, Bambang (Universiti Teknologi MARA, Shah Alam, 2017)
Managing public sector projects in Malaysia is a unique challenge. This is because of the ethical issues involved during the project procurement process. These ethical issues need attention because they will have an impact on the quality, cost and time of the project itself. The ethical issues here include conflict of interest, bid shopping, collusive tendering, bid cutting, corruption and the payment game. Extensive research has been conducted on the ethical issues in the tendering process or the award phase of project management. There is a lack of studies looking at the role of clients, including the government client, in relation to unethical practice in project procurement in the public sector. It is important to understand that ethical issues not only involve the contractors and suppliers but also the clients. A Delphi study was conducted with the assistance of a panel of experts consisting of practitioners that have expertise in the area of project governance and project procurement as well as academician, which further considered the relationship and the influence of the criteria and indicators of ethical decision making (EDM) and project governance (project criteria, organisational culture, contract award criteria, individual criteria, client’s requirements, government procedures and professional ethics). Through the identification and integration of the factors and EDM criteria as well as the project governance criteria and EDM steps for ethical issues, a PGEDM framework was developed to promote and drive consistent decision outcome in project procurement in the public sector